1974
DOI: 10.1002/chin.197436251
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESE UND CHARAKTERISIERUNG VON 5‐HYDROXY‐2‐ISOXAZOLINEN

Abstract: Hydroxylamin reagiert mit Dicarbonylverbindungen, wie z.B. (I), bei Raumtemperatur in neutralem oder basischem Medium zu den Isoxazolinolen (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the crystalline state compound 2 was found to exist as isoxazoline A. This proves to be true because the signal of sp 3 -hybrid atom C (5) at 99.4 ppm (N,O-environment) is present in its 13 C NMR spectrum recorded in the solid phase (Table 1). Immediately after the dissolution of compound 2 in CDCl 3 , a doubling of individual signals of the isoxazoline form A is observed in 1 H NMR spectrum.…”
Section: Resultsmentioning
confidence: 86%
“…In the crystalline state compound 2 was found to exist as isoxazoline A. This proves to be true because the signal of sp 3 -hybrid atom C (5) at 99.4 ppm (N,O-environment) is present in its 13 C NMR spectrum recorded in the solid phase (Table 1). Immediately after the dissolution of compound 2 in CDCl 3 , a doubling of individual signals of the isoxazoline form A is observed in 1 H NMR spectrum.…”
Section: Resultsmentioning
confidence: 86%
“…In 1974, Escale et al [25] reported the first 5-haloalkyl-5-hydroxy-4,5-dihydroisoxazole 9 (Entry 1) in the literature. To avoid dehydration to isoxazole, the compound was prepared in pyridine at a low temperature, (Scheme 2).…”
Section: Preparation Of 45-dihydroisoxazoles From -Diketonesmentioning
confidence: 99%
“…2-Amino-6-( 3,4-dioxopen ty1amino)-5-nitropyrimidin-4(3H)one (18).-Hydrochloric acid (5 ml 1 ~) was added to a solution of the pyrimidinone (14) (260 mg; 0.758 mmol) in methanol (25 ml). After being stirred for 30 min at 80"C, the reaction mixture was cooled to room temperature and then evaporated under reduced pressure to give a crude product (200 mg).…”
Section: -Acetyl-2-amino-78-dihydro-9h-pyrimido[45-b] [ 14]diazepin-4...mentioning
confidence: 99%
“…After being stirred for 30 min at 80"C, the reaction mixture was cooled to room temperature and then evaporated under reduced pressure to give a crude product (200 mg). This was washed with a mixture of methanol (10 ml) and ether (10 ml), the solvent decanted off, and the solid washed with ether and dried to give the title compound (18) as an unstable pale yellow solid (150 mg, 61%), vmax(Nujol) 1712 (22).-A solution of the pyrimidinone (14) (0.21 g, 0.612 mmol), in distilled 1,4-dioxane (15 ml) was acidified to pH 1-2 by addition of a few drops of dilute sulphuric acid. After 3 h at 60 "C with stirring, most of the starting material had been consumed and a white solid had precipitated out of the solution.…”
Section: -Acetyl-2-amino-78-dihydro-9h-pyrimido[45-b] [ 14]diazepin-4...mentioning
confidence: 99%